CHARACTERIZATION OF NON-POLAR ORGANIC COMPOUNDS FROM Padina minor MACROALGAE FROM SINGKAWANG WATERS AND ANTIBACTERIAL ACTIVITY AGAINST Staphylococcus aureus AND Escherichia coli - Fina Rika Wardani; Ajuk Sapar; Andi Hairil Alimuddin (Jurnal Ilmiah Berkala Sains dan Terapan Kimia, 2024)
Characterization of nonpolar organic compounds of macroalga Padina minor from Singkawang waters and activity against Staphylococcus aureus and Escherichia coli bacteria has been carried out. The stages of this research consisted of maceration, fractionation, phytochemical tests, characterization using FTIR and GC-MS, as well as testing the antibacterial activity with the well-diffusion method. The fractionation process produces n-hexane, dichloromethane, and methanol fractions. The n-hexane fraction was selected for packaging using gradient n-hexane: dichloromethane eluent and yielded 11 combined fractions (F1RW1-F1RW11). The combined fraction F1RW2 was separated again using n-hexane: dichloromethane eluent in a gradient manner and 18 combined fractions (F2RW1-F2RW18) were obtained. Then the F2RW4 isolate was characterized for GC-MS characterization and the F2RW3 isolate was characterized using FTIR. The FTIR interpretation results show the absorption of hydroxyl groups O-H (345.65 cm-1), C=O (1743.65 cm-1), C=C bonds (1633.71 cm-1), C-H (2926.01; 2854.01, 1438.9 and 723.31 cm-1), and C-O-C bonds (1170.79 cm-1). The results of the GC-MS analysis showed that the F2RW4 fraction had 2 main compounds, namely methyl decanoate and 11-methyl octadecenoate. The results of the antibacterial activity test showed that the methanol extract and n-hexane fraction of Padina minor were inactive against the inhibiting bacteria Staphylococcus aureus and Escherichia coli. Keywords: Padina minor, FTIR, GC-MS, Antibacterial